MITIGASI KEDIP TEGANGAN AKIBAT BEBAN TANUR BUSUR LISTRIK MELALUI KOMPENSATOR SERI: STUDI KASUS PT. KRAKATAU STEEL - Muliaty Yantahin (Program Studi Teknik Komputer, 2024)
The goal of this research project is to show how the series capacitor compensator can reduce the effects of voltage-dip problem in an electrical arc furnace operation. The case of PT. Krakatau Steel (a major steel company in Indonesia) is taken into consideration. A 195 KVA/220 arc furnace operating in the company is known to cause votage-dip problem in the surrounding distribution system supplied by a 400 MW electrical power plant. The dip is recorded as ranging from 8% to 17%.